2010
DOI: 10.1123/jab.26.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training on Muscle and Tendon in Knee Extensors and Plantar Flexors in Vivo

Abstract: The purpose of this study was to compare the effects of resistance training on muscle and tendon properties between knee extensors and plantar flexors in vivo. Twenty healthy young men voluntarily participated in this study. The subjects were randomly divided into two training groups: knee extension group (n= 10) and plantar flexion group (n= 10). They performed five sets of exercises with a 1-min rest between sets, which consisted of unilateral knee extension for the knee extension group and plantar flexion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The corresponding increase in muscle size was 6–8% in quadriceps femoris muscle volume during a 9‐week, 3 days/week strength training program . Similar gains in knee extensor strength (32–34%), muscle volume (6–8%), and 30–58% increase in vastus lateralis musculotendon stiffness were found in young males after a 12‐week knee extensor strength training program . It is also possible to achieve a 34% gain in musculotendon stiffness in 4 weeks by increasing muscle activation, rather than muscle strength .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The corresponding increase in muscle size was 6–8% in quadriceps femoris muscle volume during a 9‐week, 3 days/week strength training program . Similar gains in knee extensor strength (32–34%), muscle volume (6–8%), and 30–58% increase in vastus lateralis musculotendon stiffness were found in young males after a 12‐week knee extensor strength training program . It is also possible to achieve a 34% gain in musculotendon stiffness in 4 weeks by increasing muscle activation, rather than muscle strength .…”
Section: Discussionmentioning
confidence: 64%
“…Knee extensor strength training in humans will produce an increase in type II muscle fiber cross‐sectional area within the vastus lateralis as well as an increase in quadriceps rectus femoris volume . The associated increase in vastus lateralis musculotendon stiffness, ranging from 16% to 58% after 12 weeks of training, was more strongly associated with gains in strength than in muscle activation . While previous studies have shown that a large quadriceps force can increase the risk of ACL injury, a knowledge gap exists regarding whether achievable training‐related increases in quadriceps tensile stiffness in females via prevention programs could reduce peak ACL strain during a given pivot landing .…”
mentioning
confidence: 99%
“…Stiffness is also reported to increase with hypertrophy due to strength training (Kubo et al 2010) and with increasing muscle activation (Blanpied & Smidt 1993). Gender differences in muscle stiffness measured using different laboratory based technologies are conflicting in the literature.…”
Section: Introductionmentioning
confidence: 96%
“…Hansen et al, 2006, for example, measured the mechanical properties of the patellar tendon under loading conditions, but used a slow ramped force rise ($10 s), which resulted in a relatively low strain rate. Kubo et al (2010) and Maganaris and Paul (1999) used shorter durations of force rise ($5 s and $1 s, respectively). In light of our findings, the velocity-dependence of stiffness needs to be taken into consideration when comparing stiffness values reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, tendon stiffness has been widely studied in athletic McNair and Stanley, 1996) and clinical populations (Vaz et al, 2006;Tardieu et al, 1982). The findings of such studies have led to an enhanced understanding of how tendon stiffness influences force production (Reeves, 2006) as well as how tendon stiffness adapts to changes in loading (Kubo et al, 2010;Seynnes et al, 2009). Tendon stiffness is calculated by dividing the estimated tendon force by the tendon's elongation (Kubo et al, 2002;Maganaris and Paul, 1999).…”
Section: Introductionmentioning
confidence: 99%